Optimal Contracts when Enforcement is a Decision Variable: A Reply - Krasa, Stefan; Villamil, Anne P. (Econometrica, 2003)
IN A SIMPLE DEBT CONTRACT the investor seizes all of a firm's assets when the project return is below some threshold and receives a constant payment when the return is higher. Krasa and Villamil (2000) show that simple debt contracts that are optimal (ie., give the investor the highest payoff) among the class of deterministic contracts in the costly state verification model, and that satisfy technical conditions (Al), (A2), and a reservation utility constraint, are optimal in a more general costly enforcement model even when stochastic monitoring is possible.2 The italicized segment of this statement was not made explicit in Theorem 1 in Krasa and Villamil (2000). As Sharma points out, this restriction is necessary for the result to hold. Sharma also points out that assumption (A2) had a typographical error. Assumption (A2) in Krasa and Villamil (2000) should have appeared